Contributions of Tuan Husayn Naṣīr to Intellectual Dynamism and Heuristic Development in Malay Society - Zaini, Nor Azlinah; Che Zarrina Sa’ari; Zainal Abidin, Mohd. Syukri; Ahmad Zohdi, Ahmad Hilmi (Journal of Al-Tamaddun, 2025)
The enhancement of the significance of traditional scholars and the consolidation of the turath works of Malay heritage represent a vital asset that embodies cultural richness and provides a framework for the advancement of a nation’s civilization. Tuan Ḥusayn Naṣīr, commonly known as Tuan Ḥusayn Kedah, is a distinguished scholar who has made substantial contributions to the intellectual progression and social dynamics of society as it navigated various challenges during his time. This article employs qualitative methodologies, particularly historical analysis, drawing upon notes and historical data derived from manuscripts and other relevant works. Preliminary findings from this study reveal that Tuan Ḥusayn stands as a prominent intellectual figure in Tanah Melayu, advocating for the enhancement of national intellectualism while effectively fostering a synergistic mentality among the Malay community. The endeavours of previous scholars have significantly elevated the nation’s intellectual landscape and played a crucial role in the development of a distinguished Malay civilisation.